Cationic cellulose nano-fibers (CCNF) as versatile flocculants of wood pulp for high wet web performance. (1st February 2020) - Lu, Zonghong; An, Xingye; Zhang, Hao; Liu, Liqin; Dai, Hongqi; Cao, Haibing; Lu, Bin; Liu, Hongbin
Graphical abstract: Highlights: CCNF can act as effective flocculants of fines to form CCNF-Fines complex. CCNF with higher charge density has a stronger flocculation behavior. CCNF has little effect on the dewatering rate of wet-web. CCNF additives can improve the mechanical properties of wet web significantly. Abstract: In recent years, cellulose nano-fibers (CNF) have been regarded as renewable, promising reinforcer to enhance the strength property of paper products. In this paper, the roles of cationic cellulose nano-fibers (CCNF) as versatile flocculants of wood pulp and fines in pulp slurry for high wet web performance have been studied. It was found that CCNF can induce significantly flocculation (CCNF-Fines complex) in pulp slurries. The mechanical properties of wet web can also be improved by the addition of CCNF. The study demonstrated that CCNF can act as effective flocculants of fines and form CCNF-Fines complex for improved wet-web strength, in addition, CCNF has little effect on the dewatering rate of wet-web. CCNF is more beneficial to the wet web performance when it is in higher charge density. The research paves a way to further study the comprehensive application of CCNF in the wet-web making process for high performance.